Is negative mass media news always associated with outgroup prejudice? The buffering role of direct contact. (February 2020) - Fuochi, Giulia; Voci, Alberto; Veneziani, Chiara A.; Boin, Jessica; Fell, Benjamin; Hewstone, Miles
We examined the association of the combination of direct intergroup contact and mass media news with attitudes toward immigrants and gay people in Italy, hypothesizing that direct intergroup contact would buffer the negative association between media news and attitudes, but only when contact was intimate or positive. Measuring contact variables and attitudes toward immigrants (Study 1, N = 428; Study 2, N = 426) and gay men and women (Study 3, N = 220), we found that intimate and positive direct intergroup contact was associated with more positive attitudes toward outgroup members, whereas exposure to negative news was related to more negative attitudes. Moreover, our results supported the buffering hypothesis, as the negative association between negative news and intergroup attitudes was significantly weaker amongst respondents with higher levels of intimate and positive intergroup contact.